Peran profitabilitas pada nilai perusahaan dengan likuiditas sebagai variabel pemoderasi - Astungkara, Agni; Rois, Dimas Ilham Nur (Borobudur Accounting Review, 2023)
The corporation has responsibility to its shareholder for gaining their wealth through distribution company’s wealth. In order to fulfill this agenda for a long-term period, the company needs to develop a strategy to be able to maintain high corporate value. This study aims to find the factors that can affect the increase in firm value. This study will examine the effect of profitability and liquidity on increasing firm value. This study also examines the moderating effect of liquidity on the relationship between profitability and stock value. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period using a purposive sampling technique. Multiple regression test and moderated regression analysis (MRA) was used in this study to test the research hypothesis. The results of the study show that profitability and liquidity have a positive effect on increasing firm value. The moderating effect also has a significant influence on the relationship between profitability and firm value.